Quo vadis Wohnungspolitik? - Norbert Hiller; Daniel Schultewolter (Wirtschaftsdienst, 2014)
In den Koalitionsverhandlungen wurde ein Paket für bezahlbares Bauen und Wohnen vereinbart. Das Paket enthält unter anderem eine Mietpreisbremse, deren Wirkung die Autoren insbesondere auf längere Sicht kritisch sehen. Sie fürchten, dass dadurch weniger Wohnungen angeboten werden und ein Schwarzmarkt den Preismechanismus, der Anbieter und Nachfrager zusammenbringt, ablöst. Alle Beteiligten müssten dann Nachteile erleiden. – – The massive increase of property prices in some regions of Germany is a direct consequence of the ongoing financial and debt crisis. Low interest rates and high inflation expectations increase the demand for real estate. In addition to a potential price bubble risk, social problems arouse more and more public interest. Currently, many tenants are facing significant rent increases. Thus, the shortage of housing dominates the current housing policy discussions. The so-called package for affordable building and living includes stricter rent controls and other economic policy interventions which aim to ease the situation in the real estate market, but the interventions have the opposite effect.
Keywords: R31; R32; R38; 330; Wohnungspolitik; Preisregulierung; Marktmechanismus; Wirkungsanalyse; Deutschland